2017
DOI: 10.3847/1538-4357/aa7fef
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-scale ISM Structure and Star Formation in M51

Abstract: We compare the structure of molecular gas at 40 pc resolution to the ability of gas to form stars across the disk of the spiral galaxy M51. We break the PAWS survey into 370 pc and 1.1 kpc resolution elements, and within each we estimate the molecular gas depletion time (τ mol Dep ), the star formation efficiency per free fall time (ǫ ff ), and the mass-weighted cloud-scale (40 pc) properties of the molecular gas: surface density, Σ, line width, σ, andvir , a parameter that traces the boundedness of the gas. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
175
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 162 publications
(200 citation statements)
references
References 106 publications
(330 reference statements)
22
175
3
Order By: Relevance
“…In line with several recent studies, our observations show that current models of turbulence regulated star formation-based on idealized assumptions of cloudscale density structure and turbulence, and assuming a stationary star formation rate-do not fully capture observations across a diverse range of galactic and extragalactic star-forming environments (Lee et al 2016;Barnes et al 2017;Leroy et al 2017a;Ochsendorf et al 2017). The discrepancy may reflect observational limitations in constraining the relevant physical parameters (e.g., uncertain mass-to-light conversion and beam diluted measurements), however, it could also be of physical origin in that cloud-scale turbulent properties insufficiently reflect the dynamic "boundary" conditions of star-forming molecular clouds and that additional largescale processes are relevant (e.g., implying environmental changes in the sonic and Alfénic Mach number and the nature of turbulence driving).…”
Section: Comparison To Theoretical Modelssupporting
confidence: 70%
See 1 more Smart Citation
“…In line with several recent studies, our observations show that current models of turbulence regulated star formation-based on idealized assumptions of cloudscale density structure and turbulence, and assuming a stationary star formation rate-do not fully capture observations across a diverse range of galactic and extragalactic star-forming environments (Lee et al 2016;Barnes et al 2017;Leroy et al 2017a;Ochsendorf et al 2017). The discrepancy may reflect observational limitations in constraining the relevant physical parameters (e.g., uncertain mass-to-light conversion and beam diluted measurements), however, it could also be of physical origin in that cloud-scale turbulent properties insufficiently reflect the dynamic "boundary" conditions of star-forming molecular clouds and that additional largescale processes are relevant (e.g., implying environmental changes in the sonic and Alfénic Mach number and the nature of turbulence driving).…”
Section: Comparison To Theoretical Modelssupporting
confidence: 70%
“…These studies also found significant scatter in the SFE of individual clouds, far in excess to what the models pre-3 dict (these have been attributed to an accelerating SFR along a cloud's time evolution), and only a weak dependence of the SFE on cloud properties (Murray 2011;Evans et al 2014;Lee et al 2016;Vutisalchavakul et al 2016;Ochsendorf et al 2017). Comparing cloud population averages to the SFR-per-H 2 and ff in M51, Leroy et al (2017a) also found a poor match to the predictions of turbulent models. The sense of the correlations between cloud properties and ff in M51 appears opposite that present in some of the models.…”
Section: Introductionmentioning
confidence: 90%
“…Secondly, the strong variation of the cloud lifetime between different galaxies suggests that cloud formation and collapse does not proceed on a universal time-scale but is plausibly governed by environment, such as galactic dynamics, either by directly setting the time-scale or indirectly, by changing the properties of the clouds (e.g. Leroy et al 2017b). We will explore this hypothesis in Section 5.…”
Section: Measured Molecular Cloud Lifetimementioning
confidence: 99%
“…This is generally consistent with expectations given the dynamical state of the gas. Leroy et al (2017) showed that the depletion times for molecular gas in M51 increased if the gravitational "boundedness" (∝ Σ mol /σ CO ) decreased. Our results act in the same sense, but the weak scaling in the star formation law approach (Section 4.1) shows that this effect may manifest from how we are framing the analysis.…”
Section: Multilinear Model For Depletion Timementioning
confidence: 99%